Relevansi Kebijakan Fiskal Umar bin Khttab dengan Konteks di Indonesia - siti mudrikah (Jurnal Ilmiah Ekonomi Islam, 2021)
Financial problems, the allocation of financial funds, expenditures or state expenditures, are often a conversation that we all can’t avoid in Indonesia. Fiscal Policy is a policy that regulates the income and expenditure of state finances. Umar bin Khattab is famous for his expertise in managing the economy during his resign. He formulated state income APBN polices such as kharja and ushr through his ijtihad. He succeeded in creasing his income and trying to avoid a budget deficit by maximizing income. For state spending, Umar made expenditures to meet the needs of the people, in accordance with Islamic religious law. Expenditures used as a tool for retribution of wealth. How is the relevance of Caliph Umar’s policy to the existing fiscal policy in Indonesia. In terms meanwhile,in terms os state spending, there are some that are suitable to be applied in Indonesia, such as the benefits provided during the Umar administration, namely pension benefits.